2021
DOI: 10.1111/tri.13897
|View full text |Cite
|
Sign up to set email alerts
|

High trough levels of everolimus combined to sorafenib improve patients survival after hepatocellular carcinoma recurrence in liver transplant recipients

Abstract: Recurrence of hepatocellular carcinoma (HCC) following liver transplantation (LT) occurs in 10%-20% of patients transplanted for HCC. The treatment of HCC recurrence after LT remains a challenge. Consecutive patients who underwent LT for HCC between 2005 and 2015 at our center were recruited. Characteristics of patients with recurrence, modalities of treatment and outcome were collected retrospectively. Patient survival was analyzed according to HCC recurrence therapeutic strategy. Among 306 transplanted patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(89 reference statements)
0
7
1
Order By: Relevance
“…On the other hand, the everolimus-based regimen was also proved to be effective in patients with post-LT HCC recurrence. Patients who had high serum trough levels of everolimus (more than 5 ng/ml) had better survival compared to those treated with less than 5 ng/ml ( 34 ). In addition, early introduction of everolimus with reduced-CNIs is also associated with a significant renal benefit compared with CNsI-based immunosuppressive regime ( 35 ).…”
Section: The Status Of Immunosuppressive Agents After Ltmentioning
confidence: 99%
“…On the other hand, the everolimus-based regimen was also proved to be effective in patients with post-LT HCC recurrence. Patients who had high serum trough levels of everolimus (more than 5 ng/ml) had better survival compared to those treated with less than 5 ng/ml ( 34 ). In addition, early introduction of everolimus with reduced-CNIs is also associated with a significant renal benefit compared with CNsI-based immunosuppressive regime ( 35 ).…”
Section: The Status Of Immunosuppressive Agents After Ltmentioning
confidence: 99%
“…However, switching to mTORi-containing modifications or minimizing IS is the two preferred treatment approaches today. The literature reflects a tendency towards adding or switching to mTORi containing IS modification [24][25][26][27][28][29][30]. Even in a recent study emphasizing that minimizing IS provides a significant survival advantage, it is noteworthy that while the authors went for significant dose reduction in IS regimens containing CNIs, MMF, and steroids, they increased the use of mTORi instead of decreasing it after the diagnosis of recurrent HCC [26].…”
Section: Immunosuppressive Therapy In Patients With Hepatocellular Carcinoma Recurrence After Liver Transplantationmentioning
confidence: 99%
“…Thus, it would not be wrong to say that there is a general trend towards IS modification involving mTORi in the case of P-Tx-rHCC. It is understood from the literature that there is a tendency towards a modification in the form of transition to IS protocols containing mTORi [24][25][26][27][28][29][30]. Even in a recent study emphasizing that minimizing IS provides a significant survival advantage, it is noteworthy that, while the authors went for significant dose reduction in IS regimens containing CNIs, MMF, and steroids, they increased the use of mTORi instead of decreasing it after the diagnosis of recurrent HCC [26].…”
Section: Immunosuppressive Therapy In Patients With Hepatocellular Carcinoma Recurrence After Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of everolimus (EVR) allows less use of calcineurin inhibitors, which has led to greater preservation of renal function and reduced the risk of post‐liver transplantation (LT) recurrence of hepatocellular carcinoma 1–4 . It has been suggested that early introduction of EVR after LT is more effective than late introduction with respect to yielding these benefits 5–7 .…”
Section: Introductionmentioning
confidence: 99%